Three essays on the impact of public investments and microfinance on development in Tanzania - Malimi, Kilugala (2023)
This study examined the effects of public investments and microfinance on development in Tanzania. The study focused on three aspects of development, namely, farm labour productivity, poverty reduction, and child mortality reduction. The study used three waves of panel data from the National Panel Survey in Tanzania collected between 2008 and 2013. The study presented three papers presented in the three final chapters of this report: Chapter 2, 3, and 4.